Election cycles and systemic risk - Kladakis, George; Skouralis, Alexandros (Journal of Banking & Finance, 2026)
• Election periods are associated with heightened systemic risk by 3.57%. • Systemic risk declines pre-election in scheduled/end-of-term elections. • Post-election risk is persistent: peaks at 6 months, lasts up to a year. • Stronger effects in snap elections and when the incumbent is not re-elected. • Macroprudential policy partially buffers election-induced instability. We examine whether election periods are associated with systemic risk. Our sample comprises banks from 22 OECD economies over the period 2000 to 2023, and covers 147 national elections. The findings indicate that systemic risk increases during election and post-election periods, while it is reduced in the pre-election period in the case of end-of-term elections. More specifically, the year in which elections occur is associated with a 3.57% higher systemic risk relative to the overall average. The results can be attributed to the suppression of negative information and expansionary fiscal policies in the period before elections. Notably, the impact is more pronounced for snap elections and when the incumbent government is not re-elected. The effect is also stronger in common-law countries, where more market-based financial systems transmit political shocks more rapidly than in civil-law jurisdictions. In addition, we find that macroprudential policies, strong economic growth, trust in the current government and banks’ financial health can partially mitigate the impact of elections on systemic risk. Finally, to alleviate endogeneity concerns, we employ two instrumental variables, namely, term limits and an election uncertainty index based on Google Trends and the results hold and confirm our previous findings, further validating the robustness of our analysis.